The Regulatory Fit of Serial Entrepreneurship Intentions. Issue 3 (4th April 2016) - Simmons, Sharon A.; Carr, Jon C.; Hsu, Dan K.; Shu, Cheng
Abstract : The question why some entrepreneurs self‐select out of entrepreneurial careers following exits from successful and failed businesses is of growing interest to entrepreneurship scholars. Using two studies and Regulatory Fit Theory as the theoretical lens, we address this question. Study 1 uses the experimental vignette methodology to test whether business exits under harvest and distress conditions diminished or intensified the serial entrepreneurship intentions of 74 experienced entrepreneurs. Study 2 examines the relationship between the serial entrepreneurship intentions of 196 entrepreneurs who exited businesses and their recall of prior experiences with business success or failure. In both studies, we find evidence of a negative relationship between prevention‐focused cognition and serial entrepreneurship intentions that intensifies from the regulatory fit of distress business exits. The results of both studies suggest that the cognitive lenses used by entrepreneurs to process their business exits play important roles in their intentions to pursue serial entrepreneurship.